Effect of Graphene Nanoparticles on some Organs of Reproductive System in Male Albino Mice - Asawir Saadi AliAL-kazomy; Genan Adnan Al-Bairuty; Mohammed Mahdi Jawad (Indian Journal of Forensic Medicine & Toxicology, 2021)
Due to their exceptional physical properties, graphene nanomaterials have gained a great deal of interest in recent years for their application to state-of-the-art technology. On the other hand, nanotoxicity of graphene materials has also rapidly become a major concern, especially in the field of occupational health. There is a lack of evidence that such graphene nanomaterials influence the organs of the male reproductive system. Therefore, the goal of this study was to determine the effect of Graphene nanoparticles (GNPs) on mice body weight, reproductive organs weight and sperm quality, as well as certain reproductive organs injuries, after14 days of treatment with oral gavages of 0.1 ml of 10, 20, and 30 mg/kg of GNPs in male albino mice. The results showed a decrease in animal body weight and certain reproductive organs, as well as a decrease in the proportion of live sperm and the concentration of sperm in the tail of the epididymis and an increase in sperm abnormalities in all treatment relative to the control group. Injuries in the testes and epididymis (head and tail) were shown by histopathological analysis. This study concluded that oral GNPs gavages at various concentrations have a negative effect on the male reproductive system and can affect fertility.